Architecture : form, space, & order - Ching, Francis D. K., 1943- (Hoboken, New Jersey : Wiley, 2023)
"For more than forty years, the beautifully illustrated Architecture: Form, Space, and Order has served as the classic introduction to the basic vocabulary of architectural design. The updated and revised Fifth Edition features the fundamental elements of space and form, illustrated with many new precedents and discussions of the latest technology trends. It is designed to encourage critical thought in order to promote a more evocative understanding of architecture"--
Preface vii Introduction ix 1 Primary Elements Primary Elements 2 Point 4 Point Elements 5 Two Points 6 Line 8 Linear Elements 10 Linear Elements Defining Planes 15 From Line to Plane 14 Plane 18 Planar Elements 20 Volume 28 Volumetric Elements 30 2 Form Form 34 Properties of Form 35 Shape 36 Primary Shapes 38 Circle 39 Triangle 40 Square 41 Primary Solids 42 Regular & Irregular Forms 46 Transformation of Form 52 Dimensional Transformation 54 Geometric Transformation 58 Subtractive Form 68 Subtractive & Additive Forms 71 Additive Form 72 Centralized Form 74 Linear Form 76 Radial Form 80 Clustered Form 82 Grid Form 86 Formal Collisions of Geometry 88 Circle & Square 90 Rotated Grid 94 Articulation of Form 98 Edges & Corners 100 Corners 101 Surface Articulation 106 3 Form & Space Form & Space 118 Form & Space: Unity of Opposites 120 Form Defining Space 128 Horizontal Elements Defining Space 129 Base Plane 130 Elevated Base Plane 132 Depressed Base Plane 138 Overhead Plane 144 Vertical Elements Defining Space 154 Vertical Linear Elements 156 Single Vertical Plane 164 L-Shaped Configuration of Planes 168 L-Shaped Planes 169 Parallel Vertical Planes 174 Parallel Planes 176 U-Shaped Planes 180 Four Planes: Closure 186 Four Planes: Enlosure 190 Openings in Space-Defining Elements 194 Openings within Planes 196 Openings at Corners 198 Openings between Planes 200 Qualities of Architectural Space 202 Degree of Enclosure 204 Light 206 View 212 Ventilation 218 4 Organization Organization of Form & Space 222 Spatial Relationships 223 Space within a Space 224 Interlocking Spaces 226 Adjacent Spaces 228 Spaces Linked by a Common Space 230 Spatial Organizations 232 Centralized Organizations 234 Linear Organizations 244 Radial Organizations 254 Clustered Organizations 260 Grid Organizations 270 5 Circulation Circulation: Movement through Space 280 Circulation Elements 281 Approach 282 Entrance 290 Configuration of the Path 304 Path-Space Relationships 318 Form of the Circulation Space 322 Stairways 326 6 Proportion & Scale Proportion & Scale 336 Material Proportions 337 Structural Proportions 338 Manufactured Proportions 340 Proportioning Systems 341 Golden Section 344 Regulating Lines 348 Classical Orders 350 Renaissance Theories 356 Modulor 360 Ken 364 Anthropometry 368 Scale 371 Visual Scale 372 Human Scale 374 A Scalar Comparison 378 7 Principles Ordering Principles 382 Axis 384 Symmetry 392 Hierarchy 402 Datum 412 Rhythm 428 Repetition 429 Transformation 450 Conclusion 456 A Selected Bibliography 459 Glossary 461
Includes bibliographical references and index.
ARC
Mahmudul Islam Chowdhury
Lecturer
Department of Architecture
Course name & No. : Design l (ARC 101)
Keywords: Architecture -- Composition, proportion, etc; Space (Architecture).